ANALISIS OVERREACTION TERHADAP HARGA SAHAM MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Isnawati, Erny; Wahidahwati, Wahidahwati (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to obtain empirical evidence of the existence of overreaction in Indonesia Stock Exchange (IDX), it is indicated by the pattern of loser portfolio has abnormal return which outperforms the portfolio winner, and in order to obtain the empirical evidence of the existence of the difference of average abnormal return between loser portfolio and winner portfolio. The samples are all shares of manufacturing companies which are listed in Indonesia Stock Exchange (IDX) in 2010-2014 periods. The samples of the research have been selected by using purposive sampling method. 40 samples of companyâs shares have been selected as samples and the pooling of 200 companyâs samples have been done by using two portfolios i.e. winner portfolio and loser portfolio. The hypothesis test has been done by using different test analysis instruments i.e. Independent t-tests to test the existence of the difference of average abnormal return between loser portfolio and winner portfolio by using SPSS program and the significance level is 5%. Based on the result of the research shows, it has been found that the magnitude of overreaction is measured by using Average Abnormal Return (AAR) and Cumulative Abnormal Return (CAR) portfolio, both in winner portfolio and loser portfolio. The result of the research result shows that the overreaction can be proven by using the pattern of loser portfolio which has abnormal return which outperforms the winner portfolio. There is a significant difference of average abnormal return between loser portfolio and winner portfolio.Keywords: Overreaction, Winner Portfolio, Loser Portfolio.